KEJADIAN INFEKSI CACING GASTROINTESTINAL PADA ANJING PELIHARAAN (Canis familiaris) DI YOGYAKARTA - , KELVIANO MUQIT, drh. Hary Purnamaningsih, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Gastrointestinal parasitic diseases often attack pet dogs (Canis familiaris). Data on the prevalence of gastrointestinal parasites canât be mapped properly in Indonesia. One way to know that data is mapped incidence of gastrointestinal helminth infections in pet dogs contained in Yogyakarta. This study aimed to determine the incidence of gastrointestinal helminth infections in pet dogs in Yogyakarta. A total of 100 faecal samples were used in this study. Identification of helminth eggs using native and centrifuges methods. The result were proccessing by descriptive analysis methods. The results of research showed 50 samples (50%) were positive gastrointestinal helminth eggs. Single incidence of infection is 33% and mixed infections are 17%. Helminth infection rate found was a single infection Ancylostoma sp. as 24%, single infection of Toxocara canis as 9%, mixed infection of Ancylostoma sp. and Toxocara canis as 11%, mixed infection of Ancylostoma sp. and Dipylidium caninum as 2%, mixed infections Ancylostoma sp. and Strongyloides sp. as 2% and mixed infections Ancylostoma sp. and Taenia sp. as2%. Based on the result, it can be conluded the highest rate of infection is an infection of Ancylostoma sp comprise single infection 24% and mixed infection 17%. Efforts to suppress the incidence of infection can be done by giving proper dog care education, providing routine anthelmintic, and keeping clean the environment.